Disaster cost assessment: A case study of the potential economic impact of a nuclear accident affecting Ireland - Curtis, John; Coyne, Bryan; Morgenroth, Edgar L. W. (Statistical and Social Inquiry Society of Ireland, 2018)
We present a method for assessing the economic costs of disasters with relatively low data requirements, complementing existing methods of disaster cost assessment, such as input-output (IO) analysis and computable general equilibrium (CGE) models. The approach draws on the diffusion literature that provides insights into the temporal evolution of phenomena such as the adoption of technological innovations, which often occur via non-linear pathways. An appealing feature of the methodology is the ability to quickly conduct analysis of multiple hypothetical scenarios through the use of the same dataset. The methodology is demonstrated in a case study examining the economic impact of a hypothetical nuclear accident in northwest Europe on the Irish economy with four disaster scenarios of increasing severity. The scenario results can help inform policy makers and emergency planners who may wish to estimate costs in the wake of a disaster as well as aid planning and mitigation strategies.
read before the Society, 8 February 2018
Keywords: economic costs; cost assessment; emergency planning; 314.15